NEW DATA OF EXTENSIVE RESEARCH PROGRAM AND THE RESULTS OF STUDIES IN REAL CLINICAL PRACTICE FROM DIFFERENT COUNTRIES REAFFIRMED THE HIGH EFFICACY AND A FAVORABLE SAFETY PROFILE OF RIVAROXABAN (XARELTO®) FROM THE BAYER COMPANY PRESS RELEASE OF THE BAYER COMPANY - article editorial (Рациональная фармакотерапия в кардиологии)
.